Uma proposta de avaliação do impacto do Programa de Agricultura de Baixo Carbono (ABC +) nas emissões totais de GEE da agropecuária - Sampaio, Glauber de Queiroz (2024)
Brazilian agriculture has played a crucial role in sustainable development since the 1990s, driven by various significant events. The United Nations Conference on Environment and Development, known as the Rio-92, marked a significant milestone in this context. Additionally, the release of satellite imagery enabled better monitoring and reduction of deforestation rates in the Amazon region. During this period, the Forest Code was implemented, establishing guidelines for the preservation of native vegetation areas, and the Low Carbon Agriculture Program (Programa ABC) was created. The Programa ABC aims to promote sustainable production practices through specific financial credit lines. This study seeks to assess the impact of the Programa ABC on greenhouse gas (GHG) emissions in agricultural production. A synthetic control model was used, comparing Brazil (treated group) with the rest of the world (control group) from 2000 to 2019. The results indicated a positive impact of the program on GHG emissions after its implementation. It is estimated that if Brazil had not adopted the Programa ABC, emissions would be 27.15 percentage points higher. Additional analyses based on reliable statistical methods (Firpo, Possebom, 2018) confirm the results obtained using the methodology developed by Abadie, Diamond, and Hainmueller (2010), providing further support to the study's conclusions. In summary, the Programa ABC has played an important role in reducing GHG emissions in Brazilian agricultural production. Its specific credit lines and the adoption of sustainable practices have contributed to the promotion of sustainable development in the country's agricultural sector.